Application of Nickel-Alginate Beads in Reducing Methylene Blue Contamination in Aqueous Media - Qonita Yusry, Azwinda; Setyaningtyas, Tien; Riyani, Kapti; Amaliana Sulistyowati, Alin; Riapanitra, Anung (Indonesian Journal of Material Research, 2026)
In this study, Ni-alginate beads (Ni-ABs) were prepared to enhance their adsorption capacity for methylene blue. The adsorbent was characterized using FTIR and SEM instruments. The adsorption of Ni-ABs for methylene blue was investigated in a batch adsorption study. The adsorption conditions for Ni-ABs for methylene blue were optimized, including the pH of the methylene blue solution and contact time. The adsorption capacity of Ni-ABs for methylene blue reached 90% at pH 6 after 90 minutes of contact. The experimental results were evaluated using the Langmuir and the Freundlich isotherm models. The adsorption behavior followed the Freundlich model, suggesting multilayer adsorption. Regeneration of Ni-ABs using a 0.5 M HCl solution. The Ni-ABs exhibited good stability, with adsorption efficiencies ranging from 76–90% and desorption rates between 64–85% over five cycles. These results indicated that Ni-ABs were effective and reusable adsorbents for the selective removal of methylene blue from aqueous solutions. This study demonstrates a simple Ni-alginate bead system with high reusability as a low-cost alternative adsorbent compared to previously reported alginate-based materials.